Electromagnetic field evaluation and EMI on board during a marine geophysical data acquisition (COSMEI). (December 2019) - Di Fiore, Vincenzo; Punzo, Michele; Pelosi, Nicola; Scotto di Vettimo, Paolo; Iavarone, Michele; Budillon, Francesca; Zeni, Giovanni; Lirer, Fabrizio
Highlights: Study on the electromagnetic field onboard to evaluate EMI in critical points. The onboard acquisition systems are potentially affect by electromagnetic noise. A preliminary electromagnetic screening is advisable to optimize the ship cabling. Abstract: When performing oceanography measurements, it is critical to assess the presence of the noise sources that could affect the measured data and lead to wrong interpretation of the results. This paper report the result of an oceanography survey conducted by ISMAR-CNR, Naples, in the north-eastern marine sector of the Ischia Island and assess the influence of EMI on the measured results. The analyzed measurements of the Electric and Magnetic fields showed values of the E up to 0.82 V/m and of B up to 85 μT. By assuming a standard conductor, an inductance L up to 47 Ω on the cable corresponding to an induced electromotive force of 1184 mV was calculated. Also the experimental data show the EMI increase in site where the Pearson index correlation is higher. The results demonstrate that in an oceanographic survey planning, a preliminary electromagnetic screening is advisable to optimize the measurement setup.